Neutrophil-Derived Myeloperoxidase Facilitates Both the Induction and Elicitation Phases of Contact Hypersensitivity - Strzepa, Anna; Gurski, Cody J.; Dittel, Landon J.; Szczepanik, Marian; Pritchard, Kirkwood A.; Dittel, Bonnie N. (Frontiers in Immunology, 2021)
Background: Allergic contact dermatitis is common skin disorder affecting an estimated 15-20% of the general population. The mouse model of ACD is contact hypersensitivity (CHS), which consists of two phases: induction and elicitation. Although neutrophils are required for both CHS disease phases their mechanisms of action are poorly understood. Neutrophils release myeloperoxidase (MPO) that through oxidation of biomolecules leads to cellular damage. Objectives: This study investigated mechanisms whereby MPO contributes to CHS pathogenesis. Methods: CHS was induced in mice using oxazolone (OX) as the initiating hapten applied to the skin. After seven days, CHS was elicited by application of OX to the ear and disease severity was measured by ear thickness and vascular permeability in the ear. The role of MPO in the two phases of CHS was determined utilizing MPO-deficient mice and a specific MPO inhibitor. Results: During the CHS induction phase MPO-deficiency lead to a reduction in IL-1beta production in the skin and a subsequent reduction in migratory dendritic cells (DC) and effector T cells in the draining lymph node. During the elicitation phase, inhibition of MPO significantly reduced both ear swelling and vascular permeability. Conclusion: MPO plays dual roles in CHS pathogenesis. In the initiation phase MPO promotes IL-1beta production in the skin and activation of migratory DC that promote effector T cell priming. In the elicitation phase MPO drives vascular permeability contributing to inflammation. These results indicate that MPO it could be a potential therapeutic target for the treatment of skin ACD in humans.